Math, asked by hsahijas, 3 months ago

Solve for x and y:

2x − y = −3; 3x − 5y = −1

Answers

Answered by brinlyqueen
1

Answer:

2−=−3;3−5=−1

Step-by-step explanation:

hope it help you

Answered by BrainlyTwinklingstar
1

Answer

\sf \dashrightarrow 2x - y = -3 \: \: --- (i)

\sf \dashrightarrow 3x - 5y = -1 \: \: -- (ii)

By first equation,

\sf \dashrightarrow 2x - y = -3

\sf \dashrightarrow 2x = -3 + y

\sf \dashrightarrow x = \dfrac{-3 + y}{2}

Now, we should find the value of y by second equation.

\sf \dashrightarrow 3x - 5y = -1

\sf \dashrightarrow 3 \bigg( \dfrac{-3 + y}{2} \bigg) - 5y = -1

\sf \dashrightarrow \dfrac{-9 + 3y}{2} - 5y = -1

\sf \dashrightarrow \dfrac{-9 + 3y - 10y}{2} = -1

\sf \dashrightarrow \dfrac{-9 - 7y}{2} = -1

\sf \dashrightarrow -9 - 7y = -1 \times 2

\sf \dashrightarrow -9 - 7y = -2

\sf \dashrightarrow -7y = -2 + 9

\sf \dashrightarrow -7y = 7

\sf \dashrightarrow y = \dfrac{7}{-7}

\sf \dashrightarrow y = -1

Now, we can find the value of x by first equation.

\sf \dashrightarrow 2x - y = -3

\sf \dashrightarrow 2x - (-1) = -3

\sf \dashrightarrow 2x + 1 = -3

\sf \dashrightarrow 2x = -3 - 1

\sf \dashrightarrow 2x = -4

\sf \dashrightarrow x = \dfrac{-4}{2}

\sf \dashrightarrow x = -2

Hence, the value of x and y are -2 and -1 respectively.

Similar questions